Changes in serum RANKL and OPG with sexual development and their associations with bone turnover and bone mineral density in a cohort of girls - Lucas, R (2014)
Objectives: To characterize the variations of serum osteoprotegerin (OPG) and RANK ligand (RANKL) with sexual development in adolescent girls, and to estimate their associations with bone turnover and bone mineral density (BMD). Design and methods: We studied 300 girls evaluated at 13 and 17 years of age. Fasting blood samples were collected and the following substances were quantified: RANKL, OPG, C-terminal telopeptide of type I collagen (CTX), and procollagen type I N propeptide (PINP). BMD was measured at the distal forearm. Correlation coefficients were used to quantify associations between those variables at 13 and 17 years of age. Random-effects linear models were used to quantify associations between bone parameters and sexual development (years from menarche). Results: RANKL was positively correlated with bone resorption (CTX) in early and late adolescence (r13 = 0.15 and r17 = 0.23) and the OPG/RANKL ratio correlated inversely with CTX at 17 (r17 = − 0.24). No significant associations were found between RANKL and OPG and bone formation (PINP). In early adolescence, there was an inverse correlation of BMD with CTX (r13 = − 0.52) but no significant correlations were found between osteoclast regulators and BMD. We observed a linear decrease in serum RANKL with increasing sexual development (− 0.09 pmol/L per year, 95% CI: − 0.10, − 0.07) alongside an increase in OPG (0.02 pmol/L, 95% CI: 0.01, 0.04). Conclusions: Serum RANKL and OPG levels varied markedly with sexual development in adolescence. These cytokines were not predictive of bone turnover or BMD at 13, but serum RANKL bioactivity was associated with bone resorption in late adolescence.